Crush mechanics of thin-walled tubes - Chen, Dai-heng (CRC Press, 2016)
Thin-walled structures can be used to absorb impact energy during a vehicle collision. Crush Mechanics of Thin-Walled Tubes describes the analysis and design of these lightweight elements and thoroughly explains the deformation behaviors of thin-walled hollow members under crushing loading. The book covers, in detail, thin-walled structures-under axial compression, bending, and torsion. It provides a complete understanding of the underlying concepts and mechanisms of energy absorption components, includes analysis techniques, and covers existing theoretical approaches along with the author's research. Geared toward engineering students, practicing mechanical and structural engineers, and researchers interested in analyzing energy absorption and designing structures that may undergo impacts, this book: Addresses axial compression of circular and square tubes, and bending and torsion of tubes Summarizes the mechanism of collapse and associated calculations for the initial peak force and the average compressive force Explores two factors controlling the axial collapse of a plate Investigates systematically the deformation characteristics of corrugated tubes under axial crush Provides an understanding of the collapse behavior of members undergoing bending deformation when trying to evaluate strength and energy-absorption characteristics Looks at the bending deformation of circular and square tubes Explains the characteristic flattening phenomenon, the maximum moment in bending deformation, and the moment-rotation relation during bending collapse Discusses the collapse behavior of thin-walled structures with an open cross section during axial crushing and bending deformation Includes the proposition of a new method for evaluating the maximum bending moment of square tubes with consideration of sidewall buckling Proposes a new technique that can be used to determine the relation between the bending moment M and the rotation angle? Presents analysis methods for predicting the maximum torsion moment in each case A shelf-worthy reference showcasing structural mechanics, Crush Mechanics of Thin-Walled Tubes provides a basic understanding of the fundamental concepts and mechanisms of crushing deformations in thin-walled structures and serves as a guide for both teaching and self-study.
Keywords: Tubes.; Deformations (Mechanics); Buckling (Mechanics); Pipe.; elektronické knihy; electronic books